PET/SPECT Molecular Probes for the Diagnosis and Staging of Nonalcoholic Fatty Liver Disease - Tuo Shao PhD; Lee Josephson PhD; Steven H. Liang PhD (Molecular Imaging, 2019)
Nonalcoholic fatty liver disease (NAFLD) is a significant public health challenge afflicting approximately 1 billion individuals both in the Western world and in the East world. While liver biopsy is considered as gold standard in the diagnosis and staging of liver fibrosis, noninvasive imaging technologies, including ultrasonography, computed tomography, single-photon emission computed tomography (SPECT), magnetic resonance imaging, and positron emission tomography (PET) could offer more sensitive, comprehensive, and quantitative measurement for NAFLD. In this review, we focus on recent development and applications of PET/SPECT molecular probes that enable multispatial/temporal visualization and quantification of physiopathological progress at the molecular level in the NAFLD. We shall also discuss the limitations of current radioligands and future direction for PET/SPECT probe development.